Implementation Of Islamic Values In The 2019 Election In Indonesia - Fauza Qadriah; Raihansyah Hafidz Siswoyo (AT-TAFAHUM: Journal of Law, 2020)
This paper examines issues related to Islamic politics within the context of a culturally diverse country, particularly Indonesia, where religion and politics often intersect in shaping social and governmental structures. In Islamic perspectives, politics functions as an instrument to maintain justice, social harmony, and public welfare. However, many people perceive politics negatively, associating it with power struggles, manipulation, and practices inconsistent with moral or religious values. Consequently, politics is often viewed as something that should be avoided, despite its significant role in religious and societal life. This condition raises important questions regarding how the quality and implementation of Islamic political values influence the electoral system in Indonesia. The rapid development of Islamic political discourse, accompanied by various interpretations and hypotheses, indicates that politics grounded in Islamic principles should reflect justice, equality, deliberation, and the protection of rights for all members of society. Therefore, understanding the relationship between Islamic politics and democratic processes becomes increasingly important in contemporary Indonesia. This study employs a normative-sociological approach by analyzing legal norms alongside social realities through exploratory methods. Data were obtained from interviews with informants and supported by secondary sources, including books, scientific journals, and other academic literature. The findings are expected to provide a broader understanding of the role of Islamic political values in strengthening democratic practices and promoting a fair and inclusive electoral system in Indonesia.